(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Electronic settlement systems play a vital role in the modern economy, and are of great importance in the banking sector in particular and the economy in general. Electronic settlement systems facilitate conducting transactions quickly and easily, which saves time and effort, Previously, settlement systems in many countries, including Iraq, used traditional payment systems. The importance of the research lies in the close connection between electronic settlement systems and banking liquidity, which represents the main and important element in achieving monetary stability and then economic stability, Shedding light on a recent and vital topic that has a very important role in the banking sector, the impact of electronic settlement systems on the banking liquidity of a sample of Iraqi banks, namely the National Bank of Iraq, International Development for Investment, and Assyria International for Investment, The research is based on the hypothesis that electronic payment methods have a positive impact on the liquidity of the banks in the research sample. The most important conclusions are that there is a positive impact of electronic settlement systems on the banking liquidity of the banks studied, The most important recommendations are to work by banks operating in Iraq continuously to develop electronic settlement systems and keep pace with global developments to reach an efficient payments system that keeps pace with global developments to enable Iraqi banks to compete with banks at the regional and global levels.